Awareness of Denture Wearers about Denture Adhesives and their use- a Cross-Sectional Survey - Hammad Hassan, M. Afzal, Rabia Asad, Yousaf Jamil, Shanzey Batool, Omaima Javed, M. Hassan (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To access awareness of denture wearers about denture adhesives and their use. Methodology: The study was conducted in the prosthodontic departments of 3 private and 2 public dental institutes in Punjab participated in this study from April to December 2022 with the approval of the IRB using a questionnaire designed by the authors and administered through interviews. The questionnaire consisted of two parts that dealt with the demographics and awareness of adhesives, respectively. The data was analyzed using SPSS version 24. Results: There was no statistically significant difference between the patients of private and public dental hospitals regarding the condition of the dentures and awareness of the use of denture adhesives. A significant proportion of the respondents (34.3%) had unhygienic dentures, especially from public dental hospitals. The majority of the respondents (63%) never used denture adhesives. The most common type of adhesive used by the respondents was cream/gel (26.4%), followed by adhesive strips (10.9%).The major problem associated with the adhesives was difficulty in the removal of the adhesive (86.1%), followed by bad taste (19.9%) and halitosis (14.9%). Practical implication: Patients should be educated about the frequency, the method of application of adhesive as well as their side effects and precautions. Conclusion: Most respondents were unaware and never used denture adhesives. Patients favored adhesives that were in the cream or gel form. The most frequently mentioned issues were halitosis, taste changes, and removal difficulty. Patients should be informed about the frequency, technique, adverse effects, and precautions associated with adhesive application. Keywords: Awareness, Complete denture, Denture adhesives, Denture hygiene, Halitosis,